2002
DOI: 10.1152/ajplung.00231.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-1β on CRE-dependent gene expression in human airway smooth muscle cells

Abstract: caused a marked increase in CRE-binding protein (CREB) phosphorylation, which was attenuated by IL-1␤ (2 ng/ml). This effect of IL-1␤ was abolished by the cyclooxygenase (COX) inhibitor indomethacin. To examine CRE-driven gene expression, we transiently transfected HASM cells with a construct containing CRE upstream of a luciferase reporter gene. ISO (6 h) caused a sixfold increase in luciferase activity. IL-1␤ (24 h) alone also increased luciferase activity, although to a lesser extent (2-fold). However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Cultured murine ASM cells may represent an interesting approach to investigate the mechanisms by which TNF-␣ modulated ␤-adrenergic receptor function, but unfortunately, such an in vitro model is not available. Previous studies using cultured human ASM cells provide important observations such as the ability of TNF-␣ to decrease isoproterenol-induced adenylyl cyclase activity (19) and cAMP-dependent gene expression (36). Here we found that TNF-␣ did not attenuate the relaxant response induced by PGE 2 or forskolin, a nonreceptor-dependent relaxant agent that directly activates Fig.…”
Section: Effect Of Tnf-␣ On Murine Tracheal Smooth Musclementioning
confidence: 43%
“…Cultured murine ASM cells may represent an interesting approach to investigate the mechanisms by which TNF-␣ modulated ␤-adrenergic receptor function, but unfortunately, such an in vitro model is not available. Previous studies using cultured human ASM cells provide important observations such as the ability of TNF-␣ to decrease isoproterenol-induced adenylyl cyclase activity (19) and cAMP-dependent gene expression (36). Here we found that TNF-␣ did not attenuate the relaxant response induced by PGE 2 or forskolin, a nonreceptor-dependent relaxant agent that directly activates Fig.…”
Section: Effect Of Tnf-␣ On Murine Tracheal Smooth Musclementioning
confidence: 43%
“…We have previously reported that OSM is more effective than the other IL-6 family cytokines in causing ERK, JNK, and STAT3 phosphorylation in HASM cells (11,28). Differences in ERK and JNK activation do not appear to contribute to differences in the ability of OSM vs. other IL-6 family cytokines to induce VEGF release, since neither the MEK inhibitor U0126, which inhibits ERK phosphorylation and subsequent activation, nor the JNK inhibitor SP-600125 had any effect on OSM-induced VEGF release.…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase and b-gal were assayed as previously described. 17,28 Western blotting Confluent cells were treated with 20 ng/mL cytokines for up to 4 hours and then lysed, and solubilized proteins (30 mg per lane) were separated by means of SDS-PAGE and transferred to a BioTrace polyvinylidene difluoride membrane, as previously described. 11 The membranes were blocked and then probed with rabbit antiphosphoTyr705-STAT-3, anti-phospho-p44/p42, anti-phospho-JNK, or anti-phospho-p38 (Cell Signaling, Inc, Woburn, Mass) overnight at 4°C.…”
Section: Transfection Of Hasm Cellsmentioning
confidence: 99%